Knockdown of hsa_circ_0001275 reverses dexamethasone-induced osteoblast growth inhibition via mediation of miR-377/CDKN1B axis. - Yan Xu (Public Library of Science (PLoS), 2021)
Background Osteoporosis affects the quality of life among middle-aged and elderly individuals. In addition, dysfunction of osteoblasts can lead to the progression of osteoporosis. Circular (circ)RNAs are involved in various types of diseases, including osteoporosis. Moreover, it has been reported that hsa_circ_0001275 expression is upregulated in osteoporosis. However, the effects of hsa_circ_0001275 on the growth of osteoblasts remain unclear. Methods In the present study, the gene and protein expression levels in hFOB1.19 cells were detected via reverse transcription-quantitative (RT-qPCR) and western blot analyses, respectively. In addition, alkaline phosphatase (ALP) activity and calcium nodules were examined by ALP and alizarin red staining, respectively. Cell proliferation was measured using the Cell Counting Kit-8 assay. Cell apoptosis and cell cycle were analyzed by flow cytometry. Furthermore, dual luciferase reporter and RNA pull-down assay were used to confirm the association among hsa_circ_0001275, microRNA (miR)-377 and CDKN1B. Results DEX-induced hFOB1.19 cell growth inhibition was significantly reversed by silencing hsa_circ_0001275. Moreover, DEX significantly increased ALP activity and calcium nodules in hFOB1.19 cells, while this effect was significantly reversed in the presence of hsa_circ_0001275 small interfering RNA. In addition, miR-377 was sponged by hsa_circ_0001275 and CDKN1B was directly targeted by miR-377 in hFOB1.19 cells. Furthermore, the therapeutic effect of hsa_circ_0001275 knockdown on osteoporosis was notably reversed by miR-377 antagomir. Conclusion The data demonstrated that knockdown of hsa_circ_0001275 reversed DEX-induced osteoblast growth inhibition via activation of the miR-377/CDKN1B axis. Therefore, this study might shed new lights on the treatment of osteoporosis.